SIMULATION OF DRAFT FORCE FOR THREE TYPES OF PLOW USING RESPONSE SURFACE METHOD UNDER VARIOUS FIELD CONDITIONS - Almaliki, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
In this study a mathematical models were developed to simulate draft force for three types of plows (moldboard, chisel and disk plow). The study was carried out in the experimental field of Agricultural Machinery Department at University of Basrah, which had silty clay soil texture. Independent parameters included three levels of tillage depth (0.15, 0.20 and 0.25m), three forward speeds (0.54, 0.83 and 1.53 m/s) and two levels of cone index (550 and 980 kPa). Response Surface Method (RSM) was utilized to produce models and to analyze results. Acquired results were used to extract accurate model for draft force. The draft force increased by 114% when tillage depth increased from 15 to 25 cm. Increasing forward speed from 0.54 to 1.53 m/s led to increased draft force by 80%. The cone index had positive effect on draft force by 42% when increased cone index from 550 kPa to 980 kPa. The most influential factor in draft force is the tillage depth, followed by the forward speed and cone index. The highest draft requirements were recorded for moldboard plow, followed by chisel and disk plow. Models validation was acceptable ( R-Squared = 0.97) and the draft force could be predicted with reliability of about 95%.